Intellectual Property and Creative Machines - De Rassenfosse, Gaétan,Jaffe, Adam B.,Waldfogel, Joel (National Bureau of Economic Research, 2024)
The arrival of creative machines–software capable of producing human-like creative content–has triggered a series of legal challenges about intellectual property. The outcome of these legal challenges will shape the future of the creative industry in ways that could enhance or jeopardize welfare. Policymakers are already tasked with creating regulations for a post-generative AI creative industry. Economics may offer valuable insights, and this paper is our attempt to contribute to the discussion. We identify the main economic issues and propose a framework and some tools for thinking about them
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Künstliche Intelligenz; Kreativsektor; Urheberrecht; USA; Generative artificial intelligence; Government Policy